Profile of Science Inquiry Literacy (SIL) achievements of pre-service physics teacher using rasch model measurements - Dina Rahmi Darman; Andi Suhandi; Ida Kaniawati; Achmad Samsudin (Universitas Sultan Ageng Tirtayasa, 2024)
Pre-service physics teachers must have Scientific Inquiry Literacy (SIL) to prepare to teach physics. This research aims to describe the SIL profile of Pre-service physics teachers using the Rasch model. The mixed method with Convergent Parallel Design was chosen for this research. The mean value of the knowledge aspect is 6.1 (the top score is 35). Person measures -1.96, person separation 0.45, and person reliability 0.17. This condition shows that the consistency of the answers is still low, and the ability is low. The mean value, person measure, and separation of the skill aspect are 10.8 (the top score is 39), -1.10, and 0.00. This condition shows low ability and low diversity. The mean value for the attitude aspect is 79.5 (the top score is 108). Person size, separation, and reliability are 1.33, 2.01, and 0.8. This condition indicates a high ease of agreement on items with a wide variety and a good consistency of answers. The interviews and lesson plan analysis results show that pre-service physics teachers have yet to become accustomed to applying scientific inquiry in learning. Thus, the SIL in the knowledge and skills aspects of and the ability to design inquiry teaching still needs to be improved.